The effect of quantum nonlocality and electron nonideality on the scattering length of an electron on a helium atom in a dense plasma - Temіrbek, A.M.; Muratov, M.М.; Gabdullin, M.T.; Ramаzanov, T.S. (Recent Contributions to Physics, 2020)
In this paper, the screened Hartree – Fock potential and polarization potential are used to describe electron-helium scattering in dense plasma. Transport, partial and total elastic sections are calculated using the screened Hartree-Fock potential, polarization and optical (full) potentials. Using the data of the scattering cross-section calculations, the scattering length was found for different plasma parameters taking into account the effects of electron nonideality and without taking into account electron nonideality. The effects of quantum nonlocality and free electron correlation are taken into account in the dielectric function of the dense plasma. Plasma polarization leads to a significant increase in the transport cross-section at small wave numbers ka < 2 compared to the case of electron scattering on an isolated atom, where a is the average distance between plasma electrons. It is shown that accounting for quantum nonlocality and correlations is important for ka < 2. The effect of quantum effects on shielding was analyzed. It was shown that the plasma polarization around the atom leads to additional repulsion (attraction) between the electron (proton) and the helium atom.